An integrated membrane electrode for vanadium battery and a preparation method thereof

By adopting the preparation method of integrated film electrodes in the ion exchange membrane of vanadium flow battery, cross-linking curing reaction and acid-base pairs form a high charge density sulfonic acid polymer network structure, combined with the porous reinforcement membrane and the electrode-membrane-electrode integrated structure, the existing membrane's problems of high permeability, low stability and high cost are solved, and efficient voltage and stability improvement are achieved.

CN118970072BActive Publication Date: 2025-03-04HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411409677.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-03-04
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The ion exchange membranes of existing vanadium flow batteries have problems such as high permeability, low stability and high cost of vanadium ion, especially when taking into account vanadium resistance and ion conductivity.

Method used

An integrated film electrode for vanadium batteries and its preparation method are adopted. Through the cross-linking curing reaction between monomers and cross-linking agents and the acid-base pair interaction, a high charge density sulfonic acid polymer network structure is formed, and combined with a porous reinforcement membrane and an integrated electrode-membrane-electrode structure, the vanadium resistance and ionic conductivity of the membrane are enhanced.

Benefits of technology

It effectively improves the vanadium resistance and ionic conductivity of the film, enhances the voltage efficiency and stability of the battery, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970072B_ABST
    Figure CN118970072B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of all-vanadium liquid flow battery diaphragms, and in particular to an integrated membrane electrode for vanadium batteries and a preparation method thereof. It includes preparing a membrane-making liquid A and a membrane-making liquid B using different components. Then, a porous reinforced membrane with membrane-making liquid A on both sides and an electrode impregnated with membrane-making liquid B are prepared. Finally, an electrode-membrane-electrode integrated assembly is prepared. The present invention uses monomers with alkaline nitrogen-containing groups and cross-linking agents for cross-linking polymerization and interacts with sulfonic acid polymers with high charge density, so that the membrane has both high vanadium resistance and high ionic conductivity. At the same time, cross-linking polymerization is combined with a porous reinforced membrane to make the membrane have high stability. Finally, by preparing an electrode-membrane-electrode integrated assembly, the ion transport of ions at the interface between the membrane and the electrode is enhanced, and the voltage efficiency of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diaphragm for all-vanadium liquid flow battery, and in particular to an integrated membrane electrode for vanadium battery and a preparation method thereof. Background Art

[0002] With the rapid growth of fossil fuel consumption, environmental pollution has become increasingly serious. Therefore, there is an urgent need to develop and effectively utilize renewable energy sources such as wind energy, solar energy, and biomass. The combination of renewable resources and energy storage can improve the quality and stability of renewable energy. Vanadium flow batteries (vanadium batteries) are considered to be one of the most promising large-scale and long-term energy storage technologies for industrialization due to their advantages such as energy and power decoupling, adjustable scale, intrinsic safety and long life generated by water-based electrolytes.

[0003] Ion exchange membrane is one of the key components of vanadium flow battery, which is used to prevent the crossover of vanadium ions while allowing the transport of ions to complete the conductive circuit. The ideal membrane should exhibit low vanadium ion permeability to reduce self-discharge and achieve high Coulombic efficiency. In addition, it should exhibit high ionic conductivity to minimize the loss of voltage efficiency and achieve high voltage efficiency. Perfluorosulfonic acid membrane has been widely used in vanadium flow battery system due to its extraordinary chemical stability and good proton conductivity. However, in such systems, the key problems of severe vanadium crossover and high cost of perfluorosulfonic acid membrane need to be overcome. Non-fluorinated ion polymers, such as sulfonated polyetheretherketone, sulfonated polysulfone, sulfonated polybenzimidazole and sulfonated polyimide, are used as alternative electrolytes for vanadium flow batteries. These polymers are expected to reduce manufacturing costs while exhibiting sufficient electrochemical performance. However, non-fluorinated ion exchange membranes have disadvantages such as low stability. Among the existing modification methods, cross-linking has been shown to be one of the effective methods to improve membrane stability. Cross-linking can strengthen the polymer by forming a network between polymer chains, and can also reduce the attack from oxidants by inhibiting the expansion of the membrane. However, the cross-linked dense structure is also more likely to reduce ionic conductivity, making it difficult to strike a balance between stability and ionic conductivity. Summary of the invention

[0004] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0005] The present invention discloses an integrated membrane electrode for a vanadium battery and a preparation method thereof, which specifically comprises the following steps:

[0006] Step S1: Preparation of membrane solution: 40-60 parts by weight of monomer, 10-30 parts by weight of crosslinking agent a, 2-5 parts by weight of initiator a, and 20-40 parts by weight of ion conductive polymer a are mixed and stirred to dissolve to obtain membrane solution A; 0.1-0.5 parts by weight of crosslinking agent b, 0.001-0.005 parts by weight of initiator b, 2-10 parts by weight of ion conductive polymer b, 80-90 parts by weight of solvent, and 0.2-1 parts by weight of pore former are mixed and stirred to dissolve to obtain membrane solution B;

[0007] Step S2: porous reinforced membrane treatment: the porous reinforced membrane is ultrasonically immersed in the membrane-forming liquid A, the porous reinforced membrane after immersion is taken out, and the membrane-forming liquid A is scraped on both sides with a certain thickness using a coater to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0008] Step S3: electrode treatment: partially immersing the electrode in the film-forming liquid B along the thickness direction, taking it out, and heat-treating it to obtain an electrode immersed in the film-forming liquid B in the thickness direction;

[0009] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layers, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry to solidify, then heat and soak in 3 mol / L sulfuric acid solution for cleaning, take out and dry to obtain an integrated membrane electrode.

[0010] Preferably, in step S1, the monomer is any one of 4-vinylaniline, 2-allyl-1,4-phenylenediamine, 4-vinylpyridine, vinylimidazole, and vinylpyrrolidone; the crosslinking agent a is any one of N,N′-vinylbisacrylamide, triallylamine, 1,3-divinyl-2-imidazolidinone, and 1,3,5-triacryloylhexahydro-1,3,5-triazine; the initiator a is any one of azobisisobutyronitrile, azobisisovaleronitrile, and dimethyl azobisisobutyrate; and the ion conductive polymer a is any one of polyethylene sulfonic acid, polymethyl methacrylate sulfonic acid, and 2-acrylamido-2-methyl-1-propane sulfonic acid.

[0011] Preferably, in step S1, the crosslinking agent b is any one of poly(propylene glycol) dimethacrylate and poly(ethylene glycol) diacrylate; the initiator b is any one of azobisisobutyronitrile, azobisisovaleronitrile, and dimethyl azobisisobutyrate; the ion conductive polymer b is any one of sulfonated polyetheretherketone, sulfonated polyethersulfone, and polystyrene sulfonic acid; the solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; and the pore-forming agent is any one of PEG200, PEG400, and PPG200.

[0012] Preferably, the porous reinforced membrane in step S2 is any one of a PE porous membrane and a PP porous membrane.

[0013] Preferably, in step S2, the ultrasonic immersion treatment time is 2-4 hours; and the double-sided scraping thickness is 400-600 μm.

[0014] Preferably, in step S3, the electrode is any one of graphite felt and carbon felt.

[0015] Preferably, in step S3, the electrode immersion depth is 40-60% of the electrode thickness, and the immersion time is 10-30 min; the heat treatment temperature is 40-60° C., and the time is 20-40 min.

[0016] Preferably, in step S4, the heating and drying curing temperature is 70-90°C, and the time is 10-20 hours; the heating and soaking cleaning temperature is 60-80°C, and the time is 2-4 hours; and the drying temperature is 60-80°C, and the time is 1-2 hours.

[0017] Beneficial effects of the present invention:

[0018] 1. The monomer and cross-linking agent used in the present invention have basic nitrogen-containing groups, which can form an acid-base pair with the polymer containing sulfonic acid groups, so that the basic nitrogen-containing groups combine with the sulfonic acid groups to form a positive charge. Due to the Donnan effect, the vanadium resistance of the film can be effectively improved;

[0019] 2. The present invention fixes the sulfonic acid polymer with high charge density through the cross-linking curing reaction of the monomer and the cross-linking agent and the interaction of the acid-base pair, so that an interpenetrating network structure is formed in the membrane, and an ion transmission channel with high ion conductivity is formed along the direction of the sulfonic acid polymer chain, which can effectively improve the ion conductivity of the membrane;

[0020] 3. The present invention combines the porous reinforced membrane through cross-linking polymerization to form a dense reinforced structure, which effectively improves the stability of the membrane;

[0021] 4. The present invention forms a thin layer of ion conductive polymer on the surface of the electrode fiber and forms an electrode-membrane-electrode integrated solidified structure with the membrane, thereby enhancing the ion transport at the interface between the membrane and the electrode and improving the voltage efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of a process for preparing an integrated membrane electrode for a vanadium battery according to the present invention;

[0023] Figure 2 This is an infrared image of the PE porous membrane and the intermediate membrane layer of the integrated membrane electrode in Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the PE porous membrane and the intermediate membrane layer of the integrated membrane electrode in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0026] See also Figure 1 The present invention discloses an integrated membrane electrode for vanadium battery and a preparation method thereof. First, a monomer, a crosslinking agent a, an initiator, and an ion conductive polymer a are mixed and stirred to dissolve to prepare a membrane solution A, and a crosslinking agent b, an initiator b, an ion conductive polymer b, a solvent, and a pore forming agent are mixed and stirred to dissolve to prepare a membrane solution B. Secondly, a porous reinforced membrane with a membrane solution A on both sides and an electrode impregnated with a membrane solution B in the thickness direction are prepared. Finally, an electrode-membrane-electrode integrated membrane electrode assembly is prepared.

[0027] Embodiment 1: comprises the following steps:

[0028] Step S1: Preparation of membrane solution: 40 parts by mass of 4-vinylaniline, 10 parts by mass of N,N′-vinylbisacrylamide, 2 parts by mass of azobisisobutyronitrile, and 20 parts by mass of polyethylene sulfonic acid are mixed and stirred to dissolve to obtain membrane solution A. 0.1 parts by mass of poly(propylene glycol) dimethacrylate, 0.001 parts by mass of azobisisobutyronitrile, 2 parts by mass of sulfonated polyetheretherketone, 80 parts by mass of N,N-dimethylformamide, and 0.2 parts by mass of PEG200 are mixed and stirred to dissolve to obtain membrane solution B;

[0029] Step S2: porous reinforced membrane treatment: the PE porous membrane is ultrasonically immersed in the membrane-forming liquid A for 2 hours, the immersed PE porous membrane is taken out, and the membrane-forming liquid A is scraped on both sides by a coater to form a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0030] Step S3: electrode treatment: immerse the graphite felt partially in the film-forming liquid B along the thickness direction for 10 minutes, the electrode immersion depth is 40% of the electrode thickness, take it out, and heat treat it at 40°C for 20 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0031] Step S4: Preparation of electrode-membrane-electrode integration: a porous reinforced membrane with membrane-forming liquid A on both sides is used as an intermediate layer, and two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as outer layers, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides, heated and dried at 70°C for 10 hours, and then heated and immersed in a 3 mol / L sulfuric acid solution at 60°C for cleaning for 2 hours, and then taken out and dried at 60°C for 1 hour to obtain an integrated membrane electrode;

[0032] The infrared characterization spectrum of the PE porous membrane and the intermediate membrane layer of the integrated membrane electrode in this embodiment is as follows Figure 2 As shown, at 2921cm -1 The two characteristic absorption peaks at 2842 cm-1 and 2842 cm-1 are -CH 2 - stretching vibration peak, proving that the PE porous membrane exists as a reinforcement layer, at 3431cm -1 The two characteristic absorption peaks at 3356 cm-1 and 3356 cm-1 are the -NH 2 The stretching vibration peaks at 1663cm-1 and 1198cm-1 are the C=O and -NH- characteristic absorption peaks of the crosslinking agent N,N′-vinylbisacrylamide in the intermediate film layer of the integrated membrane electrode, indicating that the crosslinking polymerization of the two is successful. The two characteristic absorption peaks at 1013cm-1 and 1052cm-1 are the O=S=O stretching vibration peaks of polyethylene sulfonic acid in the intermediate film layer of the integrated membrane electrode, indicating that the high charge density polyethylene sulfonic acid is successfully incorporated into the crosslinking polymerization network. The scanning electron microscope images of the PE porous membrane and the intermediate film layer of the integrated membrane electrode in this embodiment are shown in Figure 2. Figure 3 As shown, the PE porous membrane presents a porous structure, while the intermediate membrane layer of the integrated membrane electrode is in a pore-filled state, indicating that the pores of the PE porous membrane are filled with cross-linked polymers.

[0033] Embodiment 2: comprises the following steps:

[0034] Step S1: Preparation of membrane solution: 45 parts by mass of 2-allyl-1,4-phenylenediamine, 15 parts by mass of triallylamine, 3 parts by mass of azobisisovaleronitrile, and 25 parts by mass of polymethyl methacrylate sulfonic acid are mixed and stirred to dissolve to obtain membrane solution A. 0.2 parts by mass of poly(ethylene glycol) diacrylate, 0.002 parts by mass of azobisisovaleronitrile, 4 parts by mass of sulfonated polyethersulfone, 82 parts by mass of N,N-dimethylacetamide, and 0.4 parts by mass of PEG400 are mixed and stirred to dissolve to obtain membrane solution B;

[0035] Step S2: porous reinforced membrane treatment: the PP porous membrane was ultrasonically immersed in the membrane-forming liquid A for 2.5 hours, the immersed PP porous membrane was taken out, and the membrane-forming liquid A was scraped on both sides by a coater to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0036] Step S3: electrode treatment: immerse the carbon felt partially in the film-forming liquid B along the thickness direction for 15 minutes, the electrode immersion depth is 45% of the electrode thickness, take it out, and heat treat it at 45°C for 25 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0037] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layers, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 75°C for curing for 12.5 hours, then heat and soak in 3 mol / L sulfuric acid solution at 65°C for cleaning for 2.5 hours, take out and dry at 65°C for 1.2 hours to obtain an integrated membrane electrode.

[0038] Embodiment 3: comprises the following steps:

[0039] Step S1: Preparation of membrane solution: 50 parts by mass of 4-vinylpyridine, 20 parts by mass of 1,3-divinyl-2-imidazolidinone, 3.5 parts by mass of dimethyl azobisisobutyrate, and 30 parts by mass of 2-acrylamido-2-methyl-1-propane sulfonic acid are mixed and stirred to dissolve to obtain membrane solution A. 0.3 parts by mass of poly(propylene glycol) dimethacrylate, 0.003 parts by mass of dimethyl azobisisobutyrate, 6 parts by mass of polystyrene sulfonic acid, 85 parts by mass of dimethyl sulfoxide, and 0.6 parts by mass of PPG200 are mixed and stirred to dissolve to obtain membrane solution B;

[0040] Step S2: porous reinforced membrane treatment: the PE porous membrane was ultrasonically immersed in the membrane-forming liquid A for 3 hours, the immersed PE porous membrane was taken out, and the membrane-forming liquid A was scraped on both sides with 500 μm of each, so as to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0041] Step S3: electrode treatment: immerse the graphite felt partially in the film-forming liquid B along the thickness direction for 20 minutes, the electrode immersion depth is 50% of the electrode thickness, take it out, and heat treat it at 50°C for 30 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0042] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layer, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 80°C for curing for 15 hours, then heat and soak in 3 mol / L sulfuric acid solution at 70°C for cleaning for 3 hours, take out and dry at 70°C for 1.5 hours to obtain an integrated membrane electrode.

[0043] Embodiment 4: comprises the following steps:

[0044] Step S1: Preparation of film-forming solution: 55 parts by mass of vinyl imidazole, 25 parts by mass of 1,3,5-triacryloylhexahydro-1,3,5-triazine, 4 parts by mass of azobisisobutyronitrile, and 35 parts by mass of polyethylene sulfonic acid were mixed and stirred to dissolve to obtain film-forming solution A. 0.4 parts by mass of poly(ethylene glycol) diacrylate, 0.004 parts by mass of azobisisobutyronitrile, 8 parts by mass of sulfonated polyetheretherketone, 88 parts by mass of N-methylpyrrolidone, and 0.8 parts by mass of PEG200 were mixed and stirred to dissolve to obtain film-forming solution B;

[0045] Step S2: porous reinforced membrane treatment: the PP porous membrane was ultrasonically immersed in the membrane-forming liquid A for 3.5 hours, the immersed PP porous membrane was taken out, and the membrane-forming liquid A was scraped on both sides with a thickness of 550 μm using a coater to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0046] Step S3: electrode treatment: immerse the carbon felt partially in the film-forming liquid B along the thickness direction for 25 minutes, the electrode immersion depth is 55% of the electrode thickness, take it out, and heat treat it at 55° C. for 35 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0047] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layer, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 85°C for curing for 17.5 hours, then heat and soak in 3 mol / L sulfuric acid solution at 75°C for cleaning for 3.5 hours, take out and dry at 75°C for 1.8 hours to obtain an integrated membrane electrode.

[0048] Embodiment 5: comprises the following steps:

[0049] Step S1: Preparation of membrane solution: 60 parts by mass of vinyl pyrrolidone, 30 parts by mass of N,N′-vinyl bisacrylamide, 5 parts by mass of azobisisovaleronitrile, and 40 parts by mass of polymethyl methacrylate sulfonic acid were mixed and stirred to dissolve to obtain membrane solution A. 0.5 parts by mass of poly(propylene glycol) dimethacrylate, 0.005 parts by mass of azobisisovaleronitrile, 10 parts by mass of sulfonated polyethersulfone, 90 parts by mass of N,N-dimethylformamide, and 1 part by mass of PEG400 were mixed and stirred to dissolve to obtain membrane solution B;

[0050] Step S2: porous reinforced membrane treatment: the PE porous membrane was ultrasonically immersed in the membrane-forming liquid A for 4 hours, the immersed PE porous membrane was taken out, and the membrane-forming liquid A was scraped on both sides by a coater to 600 μm, so as to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0051] Step S3: electrode treatment: immerse the graphite felt partially in the film-forming liquid B along the thickness direction for 30 minutes, the electrode immersion depth is 60% of the electrode thickness, take it out, and heat treat it at 60° C. for 40 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0052] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layer, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 90°C for curing for 20 hours, then heat and soak in 3 mol / L sulfuric acid solution at 80°C for cleaning for 4 hours, take out and dry at 80°C for 2 hours to obtain an integrated membrane electrode.

[0053] Comparative Example 1: comprising the following steps:

[0054] Step S1: Preparation of membrane solution: 20 parts by mass of polyethylene sulfonic acid and 60 parts by mass of pure water were mixed and stirred to dissolve to obtain membrane solution A. 0.1 parts by mass of poly(propylene glycol) dimethacrylate, 0.001 parts by mass of azobisisobutyronitrile, 2 parts by mass of sulfonated polyetheretherketone, 80 parts by mass of N,N-dimethylformamide, and 0.2 parts by mass of PEG200 were mixed and stirred to dissolve to obtain membrane solution B;

[0055] Step S2: porous reinforced membrane treatment: the PE porous membrane is ultrasonically immersed in the membrane-forming liquid A for 2 hours, and the immersed PE porous membrane is taken out to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0056] Step S3: electrode treatment: immerse the graphite felt partially in the film-forming liquid B along the thickness direction for 10 minutes, the electrode immersion depth is 40% of the electrode thickness, take it out, and heat treat it at 40°C for 20 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0057] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layers, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 70°C for curing for 10 hours, then heat and soak in 3 mol / L sulfuric acid solution at 60°C for cleaning for 2 hours, take out and dry at 60°C for 1 hour to obtain an integrated membrane electrode.

[0058] Comparative Example 2: comprising the following steps:

[0059] Step S1: Preparation of membrane solution: 40 parts by mass of 4-vinylaniline, 10 parts by mass of N,N′-vinylbisacrylamide, and 2 parts by mass of azobisisobutyronitrile are mixed and stirred to dissolve to obtain membrane solution A. 0.1 parts by mass of poly(propylene glycol) dimethacrylate, 0.001 parts by mass of azobisisobutyronitrile, 2 parts by mass of sulfonated polyetheretherketone, 80 parts by mass of N,N-dimethylformamide, and 0.2 parts by mass of PEG200 are mixed and stirred to dissolve to obtain membrane solution B;

[0060] Step S2: porous reinforced membrane treatment: the PE porous membrane is ultrasonically immersed in the membrane-forming liquid A for 2 hours, the immersed PE porous membrane is taken out, and the membrane-forming liquid A is scraped on both sides by a coater to form a porous reinforced membrane with the membrane-forming liquid A on both sides;

[0061] Step S3: electrode treatment: immerse the graphite felt partially in the film-forming liquid B along the thickness direction for 10 minutes, the electrode immersion depth is 40% of the electrode thickness, take it out, and heat treat it at 40°C for 20 minutes to obtain an electrode impregnated with the film-forming liquid B in the thickness direction;

[0062] Step S4: Preparation of electrode-membrane-electrode integration: The porous reinforced membrane with membrane-forming liquid A on both sides is used as the middle layer, and the two electrodes impregnated with membrane-forming liquid B in the thickness direction are used as the outer layers, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides. Heat and dry at 70°C for curing for 10 hours, then heat and soak in 3 mol / L sulfuric acid solution at 60°C for cleaning for 2 hours, take out and dry at 60°C for 1 hour to obtain an integrated membrane electrode.

[0063] Comparative Example 3: comprising the following steps:

[0064] Step S1: Preparation of membrane solution: 40 parts by mass of 4-vinylaniline, 10 parts by mass of N,N′-vinylbisacrylamide, 2 parts by mass of azobisisobutyronitrile, and 20 parts by mass of polyethylene sulfonic acid are mixed and stirred to dissolve to obtain membrane solution A;

[0065] Step S2: Porous enhanced membrane treatment: The PE porous membrane is ultrasonically immersed in the membrane-making liquid A for 2 hours, the immersed PE porous membrane is taken out, and 400 μm of the membrane-making liquid A is scraped on both sides using a coater, and the membrane is heated and dried at 70°C for 10 hours, and then heated and immersed in a 3 mol / L sulfuric acid solution at 60°C for 2 hours, and then taken out and dried at 60°C for 1 hour to obtain a cross-linked and cured porous enhanced ion membrane.

[0066] Experimental process and results discussion:

[0067] The ion exchange membranes or membrane electrodes prepared in Examples 1-5 and Comparative Examples 1-3 were assembled into stacks and subjected to charge and discharge tests under the same test conditions. The test charge and discharge current density was 150 mA / cm 2The battery coulombic efficiency, voltage efficiency, energy efficiency and capacity retention rate after 200 cycles were recorded. The test results are shown in Table 1.

[0068] Table 1 Battery performance test table

[0069]

[0070] As can be seen from Table 1, Examples 1-5 show higher coulombic efficiency than Comparative Example 1, indicating that the present invention can form an acid-base pair with a sulfonic acid group-containing polymer by using a monomer and a crosslinking agent with a basic nitrogen group, so that the basic nitrogen group combines with the sulfonic acid group to form a positive charge. Due to the Donan effect, the vanadium resistance of the membrane can be effectively improved, thereby achieving a higher coulombic efficiency. Examples 1-5 show higher voltage efficiency, while Comparative Example 2 cannot be charged and discharged due to the lack of an ion conductive polymer and no effective ion conductive path is formed. This indicates that the present invention fixes the sulfonic acid polymer with a high charge density through the crosslinking curing reaction of the monomer and the crosslinking agent and the interaction of the acid-base pair, so that an interpenetrating network structure is formed in the membrane, and an ion transmission channel with high ion conductivity is formed along the sulfonic acid polymer chain direction, which can effectively improve the ion conductivity of the membrane, thereby achieving a higher voltage efficiency. After 200 charge and discharge cycles of Examples 1-5, the capacity retention rate is still greater than 97%, indicating that the membrane structure remains stable after long-term cycling, and the Coulomb efficiency, voltage efficiency, etc. have not decreased much, further illustrating that the cross-linking polymerization is combined with the porous reinforced membrane to form a dense reinforced structure, which effectively improves the stability of the membrane. Examples 1-5 show a higher voltage efficiency than Comparative Example 3, indicating that the present invention enhances the ion transport at the interface between the membrane and the electrode by forming a thin layer of ion conductive polymer on the surface of the electrode fiber and forming an electrode-membrane-electrode integrated solidified structure with the membrane, thereby improving the voltage efficiency of the battery.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an integrated membrane electrode for a vanadium battery, characterized in that: The specific steps include: Step S1, preparation of membrane solution: 40-60 parts by weight of monomer, 10-30 parts by weight of crosslinking agent a, 2-5 parts by weight of initiator a, 20-40 parts by weight of ion conductive polymer a are mixed and stirred to dissolve to obtain membrane solution A; 0.1-0.5 parts by weight of crosslinking agent b, 0.001-0.005 parts by weight of initiator b, 20-40 parts by weight of ion conductive polymer b are mixed and stirred to dissolve to obtain membrane solution A; 2-10 parts by weight, 80-90 parts by weight of solvent, and 0.2-1 parts by weight of pore-forming agent are mixed and stirred to dissolve to obtain a membrane-forming solution B; the monomer is any one of 4-vinylaniline, 2-allyl-1,4-phenylenediamine, 4-vinylpyridine, vinylimidazole, and vinylpyrrolidone; the crosslinking agent a is any one of N,N′-vinylbisacrylamide, triallylamine, 1,3-divinyl-2-imidazolidinone, and 1,3,5-triacryloylhexahydro-1,3,5-triazine; the ion-conductive polymer a is any one of polyethylene sulfonic acid, polymethyl methacrylate sulfonic acid, and 2-acrylamido-2-methyl-1-propane sulfonic acid; the crosslinking agent b is any one of poly(propylene glycol) dimethacrylate and poly(ethylene glycol) diacrylate; the ion-conductive polymer b is any one of sulfonated polyetheretherketone, sulfonated polyethersulfone, and polystyrene sulfonic acid; Step S2, porous reinforced membrane treatment: ultrasonically immerse the porous reinforced membrane in the membrane-forming liquid A, take out the immersed porous reinforced membrane, and use a coater to scrape a certain thickness of the membrane-forming liquid A on both sides to obtain a porous reinforced membrane with the membrane-forming liquid A on both sides; Step S3, electrode treatment: partially immersing the electrode in the film-forming liquid B along the thickness direction, taking it out, and heat-treating it to obtain an electrode immersed in the film-forming liquid B in the thickness direction; Step S4, preparation of electrode-membrane-electrode integration: use a porous reinforced membrane with membrane-forming liquid A on both sides as the middle layer, and two electrodes impregnated with membrane-forming liquid B in the thickness direction as the outer layer, and the electrode impregnation side is close to the porous reinforced membrane with membrane-forming liquid A on both sides, heat and dry to solidify, then heat and soak in 3 mol / L sulfuric acid solution for cleaning, take out and dry to obtain an integrated membrane electrode.

2. The method for preparing an integrated membrane electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the initiator a is any one of azobisisobutyronitrile, azobisisovaleronitrile, and dimethyl azobisisobutyrate.

3. The method for preparing an integrated membrane electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the initiator b is any one of azobisisobutyronitrile, azobisisovaleronitrile, and dimethyl azobisisobutyrate; the solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; and the pore-forming agent is any one of PEG200, PEG400, and PPG200.

4. The method for preparing an integrated membrane electrode for a vanadium battery according to claim 1, characterized in that: In the step S2, the porous reinforced membrane is any one of a PE porous membrane and a PP porous membrane; the ultrasonic immersion treatment time is 2 to 4 hours; and the double-sided scraping thickness is 400 to 600 μm.

5. The method for preparing an integrated membrane electrode for a vanadium battery according to claim 1, characterized in that: In step S3, the electrode is any one of graphite felt and carbon felt; the partial immersion depth is 40-60% of the electrode thickness, and the immersion time is 10-30 minutes; the heat treatment temperature is 40-60° C., and the time is 20-40 minutes.

6. The method for preparing an integrated membrane electrode for a vanadium battery according to claim 1, characterized in that: In step S4, the heating and drying curing temperature is 70-90°C for 10-20 hours; the heating and soaking cleaning temperature is 60-80°C for 2-4 hours; and the drying temperature is 60-80°C for 1-2 hours.

7. An integrated membrane electrode for vanadium battery, characterized in that: The integrated membrane electrode is prepared by the method for preparing an integrated membrane electrode for a vanadium battery as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Polypyrrolone / sulfonated polymer composite proton exchange membrane material, and preparation method and application thereof

    CN103087337A

  • Anode / enhanced / cathode amphoteric composite membrane for all-vanadium redox flow battery and preparation method of composite membrane

    CN104282923A